2012
DOI: 10.1089/hum.2011.073
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase and Collagenase Increase the Transfection Efficiency of Gene Electrotransfer in Various Murine Tumors

Abstract: One of the applications of electroporation/electropulsation in biomedicine is gene electrotransfer, the wider use of which is hindered by low transfection efficiency in vivo compared with viral vectors. The aim of our study was to determine whether modulation of the extracellular matrix in solid tumors, using collagenase and hyaluronidase, could increase the transfection efficiency of gene electrotransfer in histologically different solid subcutaneous tumors in mice. Tumors were treated with enzymes before ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 44 publications
3
48
0
Order By: Relevance
“…HYA enzyme is successfully used in applications other than vaccination. In mice it increases the efficiency of transfection by gene ET in solid subcutaneous tumors, and it has been shown to be effective for the spreading of chemotherapeutic agents in various cancer types (Spruss et al, 1995;Klocker et al, 1998;Cemazar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…HYA enzyme is successfully used in applications other than vaccination. In mice it increases the efficiency of transfection by gene ET in solid subcutaneous tumors, and it has been shown to be effective for the spreading of chemotherapeutic agents in various cancer types (Spruss et al, 1995;Klocker et al, 1998;Cemazar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide range of industrial applications of collagenase including food industries [74], cosmetic industries [75] tannery and meat industries, [76,77] but the most significant applications of collagenase is in the field of therapeutics. Collagenases have various noninvasive therapeutic applications such as treatment of Dupuytren's and Peyronie'sdisesase, burns, wound healing, intervertebral disc herniation, chronic total occlusions, glaucoma, cartilage repair, uterine fibroid, cellulite, keloid, nipple pain and degradation of human retained placenta [69,78] and cancer gene therapy [79,80]. The collagenases can mediate tumor invasion through several mechanisms, which include constitutive production of enzyme by the tumor cells, induction of collagenase production in the neighbouring stromal cells and interactions between tumor/ stromal cells to induce collagenase production by one or both cell types.…”
Section: Applications Of Collagenases In Relation With Various Diseasesmentioning
confidence: 99%
“…As mentioned earlier, tumor extracellular matrix (ECM) is mainly composed of a dense collagen network embedded in the gel of glycosaminoglycans (GAGs), primarily hyaluronan. A number of studies demonstrating the use of collagenase, hyaluronidase and lysyl oxidase to degrade tumor ECM, as a means to improve the delivery of various therapeutics have been published in last decade [39,40]. Collagenase labeled gold nanoparticle exhibited 35% higher tumor accumulation compared with unlabeled gold nanoparticles [17].…”
Section: Oral Telmisartan Controlmentioning
confidence: 99%
“…Also, it has been shown that liposomes injected 1 h after the collagenase injection, led to approximately 1.5-fold increase in tumor uptake. Further, pretreatment with collagenase and hyaluronidase were found to enhance the transfection efficiency of plasmid DNA in subcutaneous tumor [39].…”
Section: Oral Telmisartan Controlmentioning
confidence: 99%